Words Matter: Discourse and Numeracy - Samuel L. Tunstall (Numeracy, 2016)
Here I discuss elements of critical discourse analysis (CDA) and their importance in relation to quantitative literacy (QL). Through an overview of theory, synthesis of research, and examples, I argue that the discursive nature of textbooks has a nontrivial impact on students' mathematical dispositions - an important component of QL. In particular, texts are a means of disseminating the culture of mathematics, one which has a tendency to paint mathematics as esoteric and male-dominated. Such a characterization has profound implications for the numeracy community, one of which is that we cannot assume that changes in curriculum are sufficient for effecting QL -- simply transitioning to more contextualized mathematics is not enough. Furthermore, it is critical that we examine our own discourse--whether spoken or through text--for ways in which we may be implicitly or explicitly prolong a view of mathematics in which students have little agency.